2007
DOI: 10.1093/nar/gkm569
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific splicing regulator Fox-1 induces exon skipping by interfering E complex formation on the downstream intron of human F1  gene

Abstract: Fox-1 is a regulator of tissue-specific splicing, via binding to the element (U)GCAUG in mRNA precursors, in muscles and neuronal cells. Fox-1 can regulate splicing positively or negatively, most likely depending on where it binds relative to the regulated exon. In cases where the (U)GCAUG element lies in an intron upstream of the alternative exon, Fox-1 protein functions as a splicing repressor to induce exon skipping. Here we report the mechanism of exon skipping regulated by Fox-1, using the hF1γ gene as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 40 publications
5
42
0
Order By: Relevance
“…In contrast, the mechanisms through which Fox-1/2 block exon recognition might be more heterogeneous. For example, in the context of hF1␥ gene exon 9, Fox-1 binding to a GCAUG element in intron 8 blocks prespliceosomal E-complex formation in intron 9, resulting in skipping of exon 9 (Fukumura et al 2007). We found cases (e.g., exons from Muscleblind-like genes) in which the Fox-1/2-binding sites in the UIF region are very close to the downstream 3Ј splice site.…”
Section: Mechanisms Of Fox-1/2-dependent Exon Activation and Repressionmentioning
confidence: 99%
“…In contrast, the mechanisms through which Fox-1/2 block exon recognition might be more heterogeneous. For example, in the context of hF1␥ gene exon 9, Fox-1 binding to a GCAUG element in intron 8 blocks prespliceosomal E-complex formation in intron 9, resulting in skipping of exon 9 (Fukumura et al 2007). We found cases (e.g., exons from Muscleblind-like genes) in which the Fox-1/2-binding sites in the UIF region are very close to the downstream 3Ј splice site.…”
Section: Mechanisms Of Fox-1/2-dependent Exon Activation and Repressionmentioning
confidence: 99%
“…7 Previously, we showed that Fox-1 represses the formation of E complex and U2AF binding to intron 9. 6 Therefore, it is possible that Fox-1 inhibits the binding of unknown trans-acting factors required for U1-independent 5' splice site recognition, leading to repression of the formation of ΔU1 E complex.…”
Section: Role Of U1-independent Pre-mrna Splicing In the Regulation Omentioning
confidence: 99%
“…RBFOX2 interacts with hnRNP H1 and cooperates with it and with hnRNP F to repress exon IIIc of an FGFR2 minigene by antagonizing the binding of SRSF1 (formerly SF2/ASF) (Mauger et al 2008). The C-terminal domain of RBFOX1 is critical for exon repression in an F1g minigene (Fukumura et al 2007). However, the potential involvement of this domain in alternative exon activation, or in repression of alternative exons flanked by U1-dependent introns, has not been determined.…”
Section: Introductionmentioning
confidence: 99%